(untitled) (Journal of Economic Research & Business Administration, 2016)
The article reveals the factors of financial globalization, which signifi- cantly affect the state of the modern stock exchanges. Marked by destruc- tive factors in the global economy of the XXI century can greatly worsen macroeconomic position of certain countries and affect the state of the stock market. The author analyzes the global economic environment and financial and investment sphere in the world, taking into account the specifics of the status of developed countries, developing countries and emerging economies. Revealed certain trends and dependence on the ba- sis of statistical data and examples of successful development of certain countries, formulated valid conclusions.